Small Bank Comparative Advantages in Alleviating Financial Constraints and Providing Liquidity Insurance over Time - Berger, Allen N.; Bouwman, Christa H. S.; Kim, Dasol (Review of Financial Studies, 2017)
We use novel monthly survey data from 1993 to 2012 on small business managerial perceptions of financial constraints and other conditions, matched with information on banks in their local markets. The data suggest that small banks have comparative advantages in alleviating these constraints. These advantages tend to be greater during adverse economic conditions and do not appear to decrease or increase secularly. Small banks also appear to have comparative advantages in providing liquidity insurance to small business customers of large banks experiencing liquidity shocks during financial crises. Our findings suggest a source of social costs from ongoing consolidation of the banking industry. Received December 28, 2015; editorial decision January 13, 2017 by Editor Philip Strahan.